2021
DOI: 10.3390/app11135782
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Single Pile Behaviors Due to Groundwater Level Rising

Abstract: Behaviors of the pile foundation due to groundwater level rising were analyzed by a series two-dimensional finite element analyses with fully coupled flow-deformation analysis. The different numerical models of single bore pile depth and diameter in Bangkok subsoil were represented with the parametric study. The pile–soil movement due to groundwater levels rising between numerical simulation and a previous experiment of the centrifuge test as the same condition are in good agreement. With rising groundwater le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Figure 8 shows the relationship between the total displacement and time of the surface displacement predictions of all the boreholes in Zone D. There is a tendency for rebound displacement due to groundwater recovery. As shown in Figure 9, in the same study area, Our results show soil surface behavior similar to other results, such as the results of the PLAXIS2D evaluation, which showed that soil displacement rates are equal to 0.35 cm/year from 1997 to 2037 [18]. The results of ABAQUS software produced rebound rates equal to 0.26 to 0.32 cm/year from 1997 to 2016 [19].…”
Section: Soil Surface Displacementsupporting
confidence: 86%
See 2 more Smart Citations
“…Figure 8 shows the relationship between the total displacement and time of the surface displacement predictions of all the boreholes in Zone D. There is a tendency for rebound displacement due to groundwater recovery. As shown in Figure 9, in the same study area, Our results show soil surface behavior similar to other results, such as the results of the PLAXIS2D evaluation, which showed that soil displacement rates are equal to 0.35 cm/year from 1997 to 2037 [18]. The results of ABAQUS software produced rebound rates equal to 0.26 to 0.32 cm/year from 1997 to 2016 [19].…”
Section: Soil Surface Displacementsupporting
confidence: 86%
“…As such, in this study, we focused on calculating and predicting the soil surface displacement during groundwater level recovery by hand calculation. Finally, the soil displacement result from theoretical calculation was compared with the findings of previous research from Phoban et al [18] and Saowiang and Giao [19].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The horizontal pile load test in damped sandy loam soil was followed by numerical experiments in PLAXIS 2D (PLAXIS official website) and pile performance modelling by using the finite element method [12]. The soil performance is shown in Table 1.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Previous researcher predicted that the ground displacement has rebound approximately 0.26 to 0.32 cm/yr by using ABAQUS software. [4] studied ground displacement during groundwater recovery from 1997 to 2037 also, the ground displacement has rebound around 35 percent of the maximum ground displacement of groundwater decreasing period.…”
Section: Introductionmentioning
confidence: 99%